The incidence and outcome of intraoperative hypotension in traumatic brain injured patients reported by an alternative definition of hypotension: A prospective cohort study a preliminary report - Pin-On P. (2017)
© 2017, Medical Association of Thailand. All rights reserved. Background: Hypotension is a major risk factor of morbidity and mortality in traumatic brain injured patients. According to the Brain Trauma Foundation Guideline (2007), hypotension is defined as systolic blood pressure (SBP) lower than 90 mmHg. However, some authors suggested that one absolute number could not be suitable to apply for all patients. In the present study, we had set the MAP lower than 20% from the baseline (preoperative) blood pressure as an alternative definition for hypotension. We reported the incidence of perioperative hypotension in regard to the traditional definition of hypotension (SBP lower than 90 mmHg) and an alternative definition of hypotension. Objective: To identify the blood pressure value that can be used as a surrogate to predict the 48-hour postoperative mortality of adult traumatic brain injured patients. Material and Method: We conducted a prospective cohort study. One hundred adult, traumatic brain-injured patients had been recruited. All patients were scheduled for emergency intracranial surgery. The first, in-operating room, recorded blood pressure and heart rate had been listed as their baseline vital signs. The occurrence of hypotension and the duration of hypotension in according to the traditional and an alternative definition had been recorded. The mortality rate was assessed at 48 hours postoperatively. Results: For the traditional definition of hypotension (SBP lower than 90 mmHg), the incidence of hypotension during the induction period was 22%. The mean duration of hypotension was 11±6 minutes. The incidence of hypotension during the intraoperative period was 33%. The mean duration of hypotension was 24±19 minutes. For the alternative definition of hypotension (MAP lower than 20% from baseline), the incidence of hypotension during the induction period was 58%. The mean duration of hypotension was 19±15 minutes. The incidence of hypotension during the intraoperative period was 67%. The mean duration of hypotension was 77±69 minutes. The overall mortality rate was 10%. Conclusion: The duration of intraoperative SBP lower than 90 mmHg was a significant predictor of postoperative mortality in TBI patients. The MAP reduction greater than 20% from baseline did not accurately predict the cerebral well-being so long as the baseline blood pressure was not validated.